2016
DOI: 10.3389/fmicb.2016.00520
|View full text |Cite
|
Sign up to set email alerts
|

Continuing Reassortant of H5N6 Subtype Highly Pathogenic Avian Influenza Virus in Guangdong

Abstract: First identified in May 2014 in China's Sichuan Province, initial cases of H5N6 avian influenza virus (AIV) infection in humans raised great concerns about the virus's prevalence, origin, and development. To evaluate both AIV contamination in live poultry markets (LPMs) and the risk of AIV infection in humans, we have conducted surveillance of LPMs in Guangdong Province since 2013 as part of environmental sampling programs. With environmental samples associated with these LPMs, we performed genetic and phyloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…It is probable that the reassortment pathway of the H5N6 virus was due to the epidemic of clade 2. viruses, through interaction between migratory birds and local poultry. H5N6 viruses could further exchange gene segments with viruses circulating in poultry, especially in live-poultry markets (16,35,36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is probable that the reassortment pathway of the H5N6 virus was due to the epidemic of clade 2. viruses, through interaction between migratory birds and local poultry. H5N6 viruses could further exchange gene segments with viruses circulating in poultry, especially in live-poultry markets (16,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the genetic evidence, HPAI H5N6 virus likely originated from migratory waterfowl (14). Further reassortment with other avian influenza viruses generated multiple genotypes of HPAI H5N6 viruses (15)(16)(17)(18)(19). The origins and mechanisms of dissemination of the HPAI H5N6 viruses remain to be fully elucidated, and this information is urgently needed for the development of effective disease control and prevention strategies.…”
mentioning
confidence: 99%
“…Recently, with more H5N6 genomes sequenced, it has become clear that the gene segments of these viruses derived from a variety of AIV subtypes. Specifically, the PB2 gene of some H5N6 AIVs derived from that of H6N6 viruses, while the PB1 gene originated in H3 subtype viruses (9); a novel H5N6 virus isolated from migratory waterfowl possessed a hemagglutinin (HA) gene that was related to that of H5N2 viruses (10); the internal genes of viruses isolated from two human cases in 2015 derived from H7N9/H9N2 viruses in chickens (11); human infections in Guangdong Province, China, in 2015 were due to a newly emerged H5N6 virus that was a reassortant between H6N6 and H9N2 viruses (12); and a human-associated H5N6 (clade 2.3.3.4) virus sampled in China during 2014 to 2015 was a triple reassortant derived from H6N6, H5N1 (clade 2.3.1.1), and H5N6 (2.3.4.4) viruses (13). In addition, a recent study of multiple live poultry markets (LPMs) in southern China revealed that the HA gene of H5N6 viruses derived from clade 2.3.4.4, the NA gene derived from H6N6 viruses, and all six internal gene segments had their origins in clades 2.3.4.4 and 2.3.2.1 of H9N2/H7N9 viruses (14).…”
mentioning
confidence: 99%
“…Although the potential virulence mutations are described on the basis of previous studies in animals, the pathogenesis in humans remains unknown. Because the continue evolution of H5N6 viruses in human and poultry (Yuan et al, 2016), patients they had recent history of direct contact with poultry, and drug resistance mutation have been detected in viruses isolated from both human and poultry (Shen et al, 2016), the potential for infection, outbreaks, and pandemic in humans should be closely monitored.…”
Section: Discussionmentioning
confidence: 99%